Analisis SWOT Sebagai Dasar Formulasi Strategi Inovasi Menudalam Meningkatkan Daya Saing UMKM Cafe Aloha Dompu - Putri Putri; Chairul Adhim; Lilis Marlina (Journal of Management and Creative Business, 2026)
This study aims to analyze SWOT analysis as the basis for the formulation of menu innovation strategies in increasing the competitiveness of Cafe Aloha Dompu MSMEs. The research approach uses qualitative methods with data collection techniques through observation, interviews, and documentation. The research informants consisted of 15 people consisting of owners, employees, and customers, with sample determination techniques using total sampling. The results of the internal factor analysis (IFAS) obtained a score of 2.80 which shows that Cafe Aloha Dompu has strengths in the form of strategic location, affordable prices, good product taste, and comfortable atmosphere, but still has weaknesses in the form of limited menu variety, minimal innovation, suboptimal digital promotion, and inconsistent product quality. Meanwhile, the results of the external factor analysis (EFAS) obtained a score of 2.98 which shows the opportunity of coffee consumption trends, the development of social media as a means of promotion, the large market of the younger generation, and high interest in innovative menus, in addition to threats in the form of increasing number of competitors, price competition, changes in consumer tastes, and the development of application-based delivery services. Based on the results of the SWOT analysis, Cafe Aloha Dompu is in Quadrant I so the right strategy is the SO (Strength Opportunities) strategy, which is utilizing internal strength to seize external opportunities. This strategy is realized through location optimization, price and product quality advantages, and strengthening social media-based creative promotions.